Cellular transformation by the MSP58 oncogene is inhibited by its physical interaction with the PTEN tumor suppressor - Okumura, Koichi (National Academy of Sciences, 2005)
The PTEN (phosphatase and tensin homologue) tumor suppressor protein contains a single catalytic domain with both lipid and protein phosphatase activities. The remaining C-terminal half of the PTEN protein plays a role in its stability and is mutated in many clinical cancer samples. Here, we report that the PTEN C-terminal domain physically interacts with the forkhead-associated domain of the oncogenic MSP58 protein and that this interaction requires PTEN Thr-366. We further show that while MSP58 transforms Pten–/– mouse embryo fibroblasts (MEFs), concurrent introduction of wild-type PTEN causes a dramatic reduction in the number of MSP58-induced transformed foci. This PTEN-mediated inhibition of cellular transformation requires physical interaction as evidenced by the failure of PTEN(T366A) point mutation (residing within the MSP58 interaction domain) to suppress MSP-58-driven transformation. These observations, together with the capacity of catalytically inactive PTEN mutant (G129R) to suppress MSP58 oncogenicity, support the view that the C-terminal region of PTEN directly provides a previously uncharacterized biological function in its ability to regulate cellular transformation.